Milky Way analogues in MaNGA: multiparameter homogeneity and comparison to the Milky Way. Issue 3 (11th November 2019) - Boardman, N; Zasowski, G; Seth, A; Newman, J; Andrews, B; Bershady, M; Bird, J; Chiappini, C; Fielder, C; Fraser-McKelvie, A; Jones, A; Licquia, T; et al.
ABSTRACT: The Milky Way provides an ideal laboratory to test our understanding of galaxy evolution, owing to our ability to observe our Galaxy over fine scales. However, connecting the Galaxy to the wider galaxy population remains difficult, due to the challenges posed by our internal perspective and to the different observational techniques employed. Here, we present a sample of galaxies identified as Milky Way analogues on the basis of their stellar masses and bulge-to-total ratios, observed as part of the Mapping Nearby Galaxies at Apache Point Observatory survey. We analyse the galaxies in terms of their stellar kinematics and populations as well as their ionized gas contents. We find our sample to contain generally young stellar populations in their outskirts. However, we find a wide range of stellar ages in their central regions, and we detect central active galactic nucleus-like or composite-like activity in roughly half of the sample galaxies, with the other half consisting of galaxies with central star-forming emission or emission consistent with old stars. We measure gradients in gas metallicity and stellar metallicity that are generally flatter in physical units than those measured for the Milky Way; however, we find far better agreement with the Milky Way when scaling gradients by galaxies' disc scale lengths. From this, we argue much of the discrepancy in metallicity gradients to be due to the relative compactness of the Milky Way, with differences in observing perspective also likely to be a factor.